In-Bore MR-Guided Biopsy Systems and Utility of PI-RADS. Issue 3 (June 2016) - Fütterer, Jurgen J.; Moche, Michael; Busse, Harald; Yakar, Derya
Abstract : Abstract: A diagnostic dilemma exists in cases wherein a patient with clinical suspicion for prostate cancer has a negative transrectal ultrasound-guided biopsy session. Although transrectal ultrasound-guided biopsy is the standard of care, a paradigm shift is being observed. In biopsy-naive patients and patients with at least 1 negative biopsy session, multiparametric magnetic resonance imaging (MRI) is being utilized for tumor detection and subsequent targeting. Several commercial devices are now available for targeted prostate biopsy ranging from transrectal ultrasound-MR fusion biopsy to in bore MR-guided biopsy. In this review, we will give an update on the current status of in-bore MRI-guided biopsy systems and discuss value of prostate imaging-reporting and data system (PIRADS).